DESKRIPSI JABATAN FUNGSIONAL DOSEN DI LINGKUNGAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNTAN - Subarjo Subarjo Subarjo (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Functional positions provide opportunities for lecturers to occupy structural positions in higher education. Functional positions also provide authority to guide students on their final assignments and, no less importantly, impact the opportunity to participate in research grants. The most important thing is a reward, both moral and financial, for the functional position. Busy lecturers ultimately get dragged into academic routines, so they sometimes forget the status of the functional position they hold. The aim of this research is to determine the functional positions of lecturers within the FKIP UNTAN environment. The research sample was FKIP UNTAN lecturers in 28 study programs for three years (2019–2021). Data is a file obtained from the civil service staff. Data analysis was carried out using descriptive statistics. The research results show that the teaching staff positions are 9.92%, expert assistants are 23.57%, lecturers are 25.79%, associate professors are 36.56%, and professors are 4.16%. Based on these results, the needs for professors and associate professors can still be increased, and the position of teaching staff can be increased to expert assistant and so on in stages